Learning experiences on role‐emerging placements: An exploration from the students' perspective. Issue 6 (1st September 2013) - Dancza, Karina; Warren, Alison; Copley, Jodie; Rodger, Sylvia; Moran, Monica; McKay, Elizabeth; Taylor, Ann
<x xml:space="preserve">Abstract</x> Background/aim Occupational therapy educators are challenged to provide students with practical experiences which prepare them for ever changing health‐care contexts on graduation. Role‐emerging placements have been widely used internationally to help meet this challenge, but research into the learning experiences of students during these innovative placements is limited. This research investigated the enablers and barriers to learning from the perspectives of students on such placements from two European universities. Methods Two separate qualitative studies tracked 10 final year students. Interviews explored their learning experiences prior to, during and after an eight‐ or 10‐week role‐emerging placement in a range of settings. Results Four themes emerged, which were (1) adapting to less doing, more thinking and planning; (2) understanding the complexity of collaboration and making it work; (3) emotional extremes; and (4) realising and using the occupational therapy perspective. Conclusions These placements presented a 'roller coaster' of authentic learning experiences which created the opportunity for students to use occupation in practice and develop skills for collaborative working in an interprofessional environment. Whereas students viewed their role‐emerging placement experiences positively, challenges included the emotional responses of students and placement pace. Findings suggest the need for supportive student placement experiences in both established and role‐emerging areas to prepare students for a range of opportunities in an uncertain future.